PROBLEMATIKA TUMPANG TINDIH SERTIFIKAT HAK ATAS TANAH DALAM SISTEM PENDAFTARAN TANAH DI INDONESIA - Filex Melanton Labobar; Emilianus Jimmy Ell; Agustinus Luturmas; Imanuel Inriyanto Ruslak Hammar (PATRIOT, 2026)
Overlapping land title certificates remain a recurring issue within Indonesia's land registration system, undermining legal certainty for land rights holders. The existence of two or more certificates for the same plot of land not only triggers protracted disputes but also causes economic losses, hinders investment, and erodes public trust in the land administration system. This situation indicates that the objectives of land registration—as mandated by the Basic Agrarian Law and Government Regulation Number 24 of 1997—have not yet been fully realized. This study aims to analyze the factors causing overlapping land title certificates, examine the responsibilities and performance of the National Land Agency in preventing and resolving disputes involving multiple certificates, and formulate measures to ensure legal certainty for land rights holders. The study employs a normative legal research method utilizing statutory, conceptual, and case approaches. Primary legal materials include the 1945 Constitution of the Republic of Indonesia, Law Number 5 of 1960 concerning Basic Regulations on Agrarian Principles, Government Regulation Number 24 of 1997 concerning Land Registration, and other relevant land regulations. Secondary legal materials were obtained from books, scholarly journals, court rulings, and relevant research findings. A qualitative analysis was conducted by examining legal norms, legal theories, and research data related to disputes over multiple certificates. The findings indicate that overlapping land title certificates stem from various factors, including land administration errors, a lack of integration in land data, document forgery, weak internal oversight, and the characteristics of the "negative publication system with positive tendencies," which still leaves room for disputes regarding issued certificates. In its efforts to prevent and resolve disputes, the National Land Agency has strengthened surveying and mapping, verified land data, implemented the Complete Systematic Land Registration program, digitized land services, conducted dispute mediation, revoked certificates with administrative flaws, and executed court rulings. Meanwhile, efforts to ensure legal certainty for land rights holders must be pursued by strengthening the electronic land system, integrating the national land database, enhancing oversight and accountability in land administration, refining land registration regulations, and optimizing dispute resolution mechanisms that guarantee fairness and legal protection for the public.